2009
DOI: 10.1101/gad.1770509
|View full text |Cite
|
Sign up to set email alerts
|

Promoter-specific control of E. coli RNA polymerase by ppGpp and a general transcription factor

Abstract: The stringent response of Escherichia coli reflects a global influence of the nucleotide ppGpp on gene expression in response to nutrient starvation. For critical elements of the response, the target of ppGpp is RNA polymerase, which can be either repressed or activated in a promoter-dependent way. A small protein, DksA, which binds in the secondary channel of RNA polymerase, possibly along with other general regulatory factors, contributes to ppGpp-dependent transcription regulation. Rutherford and colleagues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Stringent response regulation of glycerol and chitobiose gene expression might be mediated directly at the level of transcription by interactions of (p)ppGpp and DksA with the RNA polymerase complex at the glycerol and chitobiose gene promoters [ 1 , 14 , 83 ]. That there were no differences in transcriptional levels of rpoS , rpoN , bosR , and rrp2 between the rel Bbu mutant and wild type B .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stringent response regulation of glycerol and chitobiose gene expression might be mediated directly at the level of transcription by interactions of (p)ppGpp and DksA with the RNA polymerase complex at the glycerol and chitobiose gene promoters [ 1 , 14 , 83 ]. That there were no differences in transcriptional levels of rpoS , rpoN , bosR , and rrp2 between the rel Bbu mutant and wild type B .…”
Section: Discussionmentioning
confidence: 99%
“…That there were no differences in transcriptional levels of rpoS , rpoN , bosR , and rrp2 between the rel Bbu mutant and wild type B . burgdorferi under any experimental conditions examined suggests a direct interaction of (p)ppGpp with the RNA polymerase complexes at the glp and chitobiose operon promoters or interactions with still uncharacterized regulators [ 1 , 14 , 48 , 50 , 83 ]. The B .…”
Section: Discussionmentioning
confidence: 99%
“…In a view of the fact that DksA enhances negative and positive effects of ppGpp on promoters’ activities, it was proposed that DksA plays a role as a cofactor of the stringent response (68,15). Nevertheless, recent reports indicated that DksA and ppGpp can have independent or opposing effects (1620) or their effects may very specifically depend on the individual promoters, holoenzymes involved or stress conditions (21).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the accumulation of unusual guanosine nucleotides, collectively called (p)ppGpp, is the hallmark of the stringent response of E. coli [15-18] (Figure 1). Such accumulation is known to be controlled by the activity of two enzymes, the ribosome-bound RelA enzyme (ppGpp synthetase I) that synthesises (p)ppGpp nucleotides upon the depletion of amino acids [19] and the bifunctional SpoT enzyme (ppGpp synthetase II) that is responsible for maintaining the intracellular levels of (p)ppGpp nucleotides via enzymatic degradation [20].…”
Section: Introductionmentioning
confidence: 99%